Searching for the Appropriate Editorial Technique: The Case of Gädlä Śärṣä Ṗeṭros - Hummel, Susanne (Aethiopica, 2015)
This article shows the development of a method of editing a hagiographic work at first known by a single text witness only. The protagonist, the monk Śärṣä Ṗeṭros, lived in the fifteenth century and founded the monastery of Däbrä Wärq (eastern Goǧǧam) where he is still venerated as saint. The work is named Gädlä Śärṣä Ṗeṭros and contains the saint’s Vita, his miracles and a mälkǝʿ-hymn. After a brief introduction to the work’s content and its narrative structure, the article reflects the first considerations and ideas on how the work could be edited taking into account the main principles of a scholarly edition and the challenges of working with a single text witness. The article presents the then current state of research while the Addendum outlines substantial changes surfaced soon after the 18th International Conference of Ethiopian Studies, Dǝrre Dawa 2012.